Dynamic chaos generated by linear systems - Buts, V.A. (Вопросы атомной науки и техники, 2012)
It is shown that regimes with chaotic behavior are also inherent in linear systems. A dynamic chaos which can arise in essentially quantum systems (not quasi-classical) is of special interest. In particular, it is shown that the diffusion of quantum systems in the energy space can be considerably more effective than transitions at multiphoton processes. It is shown that taking into account the singular solutions allows to realize regimes with chaotic behavior even in systems with "one'' degree of freedom.